2010
DOI: 10.1161/hypertensionaha.110.150235
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Blood Pressure in Offspring Born Premature to Hypertensive Pregnancy

Abstract: Abstract-Offspring born to mothers with hypertensive pregnancy have higher childhood blood pressure. We hypothesized this relates to prenatally programmed differences in the underlying vascular pathophysiology of the offspring and that these would be most apparent in those born preterm because of severe hypertension. We carried out a 20-year follow-up study of 71 subjects born preterm, 19 to a hypertensive pregnancy and 52 to a normotensive pregnancy. Findings were compared with 38 subjects born at term to unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
110
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(121 citation statements)
references
References 63 publications
(60 reference statements)
6
110
1
3
Order By: Relevance
“…This hypothesis is consistent with what is known about the biological process of arterial stiffening 8 and clinical research that highlights regional changes in arterial stiffness 9 and selective derangement in parameters of vascular function in younger cohorts. 9,10 Arterial stiffness reflects a multifactorial interplay of structural and cellular changes in the vessel wall, and is not uniform within the arterial tree.…”
Section: Variability In the Process Of Arterial Stiffeningsupporting
confidence: 89%
See 1 more Smart Citation
“…This hypothesis is consistent with what is known about the biological process of arterial stiffening 8 and clinical research that highlights regional changes in arterial stiffness 9 and selective derangement in parameters of vascular function in younger cohorts. 9,10 Arterial stiffness reflects a multifactorial interplay of structural and cellular changes in the vessel wall, and is not uniform within the arterial tree.…”
Section: Variability In the Process Of Arterial Stiffeningsupporting
confidence: 89%
“…9,10 Arterial stiffness reflects a multifactorial interplay of structural and cellular changes in the vessel wall, and is not uniform within the arterial tree. 5 The structural proteins elastin and collagen are the primary mediators of arterial wall compliance and stability.…”
Section: Variability In the Process Of Arterial Stiffeningmentioning
confidence: 99%
“…23 Another recent study with similar findings suggests that endothelial dysfunction in the offspring is either persistent after the preeclampsia in pregnancy or there is a heritable predisposition to endothelial dysfunction in both mother and child. 24 The elevated BP in the off- spring of preeclampsia pregnancies may also simply reflect a familial aggregation of this phenotype. 8 This strong familial aggregation of BP among the offspring of mothers with hypertension of pregnancy suggests that perhaps there are possibility of additional specific hereditary factors and intrauterine environmental effects.…”
Section: Discussionmentioning
confidence: 99%
“…To date, studies have reported increased aortic stiffness in children as early as 7 to 14 years of age that were born moderately or very preterm. [29][30][31] In addition, adolescents and young adults born preterm were found to have smaller aortic, carotid, and brachial artery luminal diameters compared with controls born at term 18,32,33 ; aortic growth was shown to be impaired from the early neonatal period after preterm birth. 34 Furthermore, in a sheep model of moderate preterm birth, evidence of vascular injury to the ascending aorta was observed in animals examined at 11 weeks postnatal age.…”
Section: Vascularmentioning
confidence: 98%
“…35 Carotid intima-media thickness, an early marker of atherosclerosis and nonatherosclerotic remodeling, has also been shown to be increased in relation to lumen diameter. 31,33 The effect of preterm birth on microvascular development has also been highlighted by studies showing reduced retinal vascular caliber and density (independently of retinopathy of prematurity), as well as reduced cutaneous capillary density in children and young adults born very preterm. 19,36 To date, studies assessing endothelial function have shown either no effect 18,19,31 or diminished brachial artery flowmediated dilatation 37 in children and young adults born preterm; whether changes will be apparent later in adult life remain to be evaluated.…”
Section: Vascularmentioning
confidence: 99%